Hybrid Rydberg quantum gate for quantum network - Yubao Liu; Lin Li; Yiqiu Ma (Physical Review Research, 2022)
The high-fidelity storage, distribution, and processing of quantum information prefers qubits with different physical properties. Thus hybrid quantum gates interfacing different types of qubits are essential for the realization of complex quantum network structures. A Rydberg-atom-based physical quantum controlled-Z (CZ) gate is proposed to hybridly process the polarization-encoded single-photon optical qubit and the “Schrödinger cat” microwave qubit. The degradation of the fidelity under the influence of various noise channels, such as microwave cavity loss, spontaneous emission of atom states, and nonadiabaticity effect, etc., has been analyzed through detailed theoretical analysis by deriving the input-output relation of qubit fields. The feasibility and the challenges of the protocol within current technology are also discussed by analyzing the possible experimental parameter settings. Our work opens prospects for future large-scale quantum architecture based on hybrid quantum modules.